Retraction Note: Optimizing callogenesis in five potential medicinal herbs for the bioactive constituents: a sustainable approach to pharmaceutical production - Muhammad Wasim Haider; Muhammad Nafees; Maryyam Bint-e-Tariq; Umar Farooq; Tanveer Hussain; Taki Demir; Asad Masood; Muhammad Samsam Raza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Ozhan Simsek; Temoor Ahmed; et al. (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Application of cold plasma for enhancing phenolic extraction from microalgal biomass - Tracy Chen; Armin Mirzapour-Kouhdasht; Juan Antonio Velasquez; Lavanya Reddivari; Andrea M. Liceaga; Halis Simsek; Jen-Yi Huang (Algal Research, 2026)

Managing water deficit in wheat through mulches and irrigation techniques in semi-arid regions - Salman Ahmad; Muhammad Aown Sammar Raza; Muhammad Ali; Rashid Iqbal; Muhammad Usman Aslam; Monika Toleikiene; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Imran Haider; Muhammad Zain; Saltanat Aghayeva; Ozhan Simsek; et al. (Cereal Research Communications, 2025)

Epidemiological, clinical and microbiological aspects of infective endocarditis in Türkiye - Elif M. Saricaoglu; Seniha Basaran; Derya Seyman; Merve Arslan; Serpil Ozkan-Ozturk; Yasemin Tezer-Tekce; Yesim Uygun-Kizmaz; Nuran Sari; Denef Berzeg-Deniz; Alpay Azap; Serap Simsek-Yavuz; Ozlem Kurt-Azap (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Purpose Infective endocarditis (IE) is a evolving disease with a shifting epidemiology and disease burden over time. This study aimed to compare the epidemiological and clinical aspects of IE over three time periods across eleven years. Methods This was a retrospective cohort, multicenter study conducted in Türkiye, comparing three periods: 2013–2016, 2017–2020, and 2021–2023. Epidemiological and microbiological characteristics, as well as patient outcomes, were analyzed and compared across these periods. Results A total of 1,044 patients diagnosed with IE were included. The median (Q1-Q3) age was 57 (44–68) years, with an increasing pattern ( p < 0.001). Throughout the study period, the prevalence of intracardiac devices increased, whereas the prevalence of degenerative and congenital heart diseases declined. Among all patients, the most frequently identified pathogens were staphylococci (36.4%), followed by streptococci (14.0%) and enterococci (11.9%). Throughout the three periods, there was a significant increase in staphylococci, with S. aureus emerging as the predominant pathogen in all type IE. The in-hospital mortality rate among all patients was 22.5%. Independent risk factors for in-hospital mortality included ≥ 65 age(OR = 1.9), chronic kidney disease (OR = 1.9), nosocomial acquisition (OR = 2.1), Candida spp. infection (OR = 2.9), prosthetic valve IE (OR = 1.9), vegetation size > 15 mm (OR = 1.6), and central nervous system emboli (OR = 2). Conclusion The epidemiology of IE is undergoing significant changes, leading to shifts in microbiological profiles and clinical presentations. Effective management of IE should be guided by established clinical guidelines while integrating up-to-date epidemiological data to ensure comprehensive and evidence-based patient care.

Starch digestion: A comprehensive update on the underlying modulation mechanisms and its in vitro assessment methodologies - Daniela Freitas; Athina Lazaridou; Dorine Duijsens; Kali Kotsiou; Kendall R. Corbin; Marilisa Alongi; Natalia Perez-Moral; Sebnem Simsek; Sedef Nehir El; Shannon Gwala; Sibel Karakaya; Steven Le Feunteun; et al. (Trends in Food Science & Technology, 2025)

RETRACTED ARTICLE: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Optimizing callogenesis in five potential medicinal herbs for the bioactive constituents: a sustainable approach to pharmaceutical production - Muhammad Wasim Haider; Muhammad Nafees; Maryyam Bint-e-Tariq; Umar Farooq; Tanveer Hussain; Taki Demir; Asad Masood; Muhammad Samsam Raza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Ozhan Simsek; Temoor Ahmed; et al. (Genetic Resources and Crop Evolution, 2025)

Evaluation of genetic diversity and population structure of the Chinese chestnut (Castanea mollissima) by using NR-SSR markers - Saman Zulfiqar; Muhammad Mahran Aslam; Allah Ditta; Rashid Iqbal; Abd El-Zaher M. A. Mustafa; Mohamed S. Elshikh; Muhammad Uzair; Saltanat Aghayeva; Muhammad Qasim; Sezai Ercisli; Ozhan Simsek; Tolga Izgu; et al. (Genetic Resources and Crop Evolution, 2025)

Effects of cooking and market classes on nutritional and antioxidant properties of dry bean flours and soluble dietary fiber-rich fractions - Ana M. Magallanes López; Osvaldo H. Campanella; Senay Simsek (Bioactive Carbohydrates and Dietary Fibre, 2024)

Ex vivo disease modelling of Rett syndrome: the transcriptomic and metabolomic implications of direct neuronal conversion - Beren Karaosmanoglu; Gozde Imren; M. Samil Ozisin; Tuba Reçber; Pelin Ozlem Simsek Kiper; Goknur Haliloglu; Mehmet Alikaşifoğlu; Emirhan Nemutlu; Ekim Z. Taskiran; Gulen Eda Utine (Molecular Biology Reports, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Inactivation of Salmonella and Shiga-toxin producing Escherichia coli on soft wheat kernels using vacuum steam pasteurization - Yawei Lin; Quincy Suehr; Kirk Dolan; Senay Simsek; Teresa M. Bergholz (International Journal of Food Microbiology, 2023)

Fate of salmonella and shiga-toxin producing Escherichia coli on wheat grain during tempering - Yawei Lin; Senay Simsek; Teresa M. Bergholz (Food Microbiology, 2023)

Exome sequencing unravels unexpected differential diagnoses in individuals with the tentative diagnosis of Coffin–Siris and Nicolaides–Baraitser syndromes - Nuria C. Bramswig; Hermann-Josef Lüdecke; Yasemin Alanay; Beate Albrecht; Alexander Barthelmie; Koray Boduroglu; Diana Braunholz; Almuth Caliebe; Krystyna H. Chrzanowska; Johanna Christina Czeschik; Sabine Endele; Elisabeth Graf; et al. (Human Genetics, 2015)

Clinical and mutation data in 12 patients with the clinical diagnosis of Nager syndrome - J. C. Czeschik; C. Voigt; Y. Alanay; B. Albrecht; S. Avci; D. FitzPatrick; D. R. Goudie; U. Hehr; A. J. Hoogeboom; H. Kayserili; P. O. Simsek-Kiper; L. Klein-Hitpass; et al. (Human Genetics, 2013)

Apoptosis in diabetes - Paul A. J. Krijnen; Suat Simsek; Hans W. M. Niessen (Apoptosis, 2009)

A quantitative trait locus on chromosome 5B controls resistance of Triticum turgidum (L.) var. diccocoides to Stagonospora nodorum blotch - J. L. Gonzalez-Hernandez; P. K. Singh; M. Mergoum; T. B. Adhikari; S. F. Kianian; S. Simsek; E. M. Elias (Euphytica, 2009)

Acute Toxicity of Dichlorvos on Fingerling European Catfish, Silurus glanis - M. S. Ural; S. Simsek Koprucu (Bulletin of Environmental Contamination and Toxicology, 2006)

The human cytomegalovirus immediate early enhancer-promoter is responsive to activation by the adenovirus-5 13S E1A gene - D. M. Olive; W. Al-Mulla; M. Simsek; S. Zarban; W. Al-Nakib (Archives of Virology, 1990)